Bygdeidyllens gotiska maskineri: Nationell identitet och fluktuerande bytesvärde i Fredrika Bremers i Dalarne - Haux, Caroline (Tidskrift för litteraturvetenskap, 2018)
The Country Life Novel’s Gothic Machinery.National Identity and Fluctuating Exchange Value in Fredrika Bremer’s Life in Dalecarlia When Fredrika Bremer in her novel I Dalarne (1845) (Life in Dalecarlia) represents Falu copper mine as the horrific ruin of classic gothic tales – a vast and life-threatening void, the home of dreadful crimes and secret passions – this is paradoxically part of a nationalistic literary strategy. Simultaneously, though, the novel writes the nation as a pastoral on country life and mores of the peasantry. The article investigates how the gothic and the pastoral idyllic respectively establish the nation and national identity on their separate terms and in relation to each other in accordance with their own particular inner logic. The idyllic streaks both manifests and problematize local place as foundation for national identity, while the gothic exposes identity as arbitrary, and thereby subverts the notion of a citizen subject. This duality is linked to a market-based model of identity which the article argues is actualized by the novel itself. The condition of possibility is the emerging consumer society and the beginnings of industrialism – breakthrough changes which in the novel are thematized as tensions between tradition and modernity. At stake in this field of tension between the idyllic and the gothic stands the nation as a community of citizens: a collective subject.